DETERMINATION OF ACCEPTABLE PLANTING TIMES TO ENSURING HIGHER YIELD OF PUMPKINS IN REPEATED CROPPING - Turamatov Rustam Gopurovich; Shokirov Alisher Joraboyevich (Modern American Journals, 2025)
In the second crop, the highest marketable yield of the “Shirintoy” and “Palov kadu 268” pumpkin varieties was formed at the sowing date of June 1 (respectively: 34.1 and 38.2 t/ha), and the highest net income and profitability were obtained at the sowing date of June 1 (respectively: 44.4 and 33.2 mln soums; 186.0 and 138.2%).
Keywords: Repeated crop, variant, cultivar, leaves, leaf height, main stem, yield, biometric, sowing date, fruit flesh, fruit quantity, marketable, net income, profitability.